Small renal cell carcinoma: oncological outcome with tumour size - Pahernik, Sascha; Huber, Johannes; Pfitzenmaier, Jesco; Haferkamp, Axel; Hohenfellner, Markus (Scandinavian journal of urology and nephrology, 2011)
OBJECTIVE: The aim of the study was to analyse oncological outcomes of patients with renal cell carcinoma (RCC) up to 4 cm in diameter. - MATERIAL AND METHODS: A consecutive series of 396 patients with small RCC was analysed. Tumours were stratified by diameter into three groups: 2 cm (n = 68) for tumours up to 2 cm, 3 cm (n = 172) for tumours between 2.1 and 3.0 cm, and 4 cm (n = 156) for tumours between 3.1 and 4.0 cm in diameter. - RESULTS: Tumour stages were distributed into pT1a in 95.6%, 91.9% and 87.0% and into pT3 in 4.4%, 8.1% and 13.0% for the 2 cm, 3 cm and 4 cm groups, respectively. Metastases at the time of diagnosis were found in 2.9% (n = 2), 7.5% (n = 13) and 9.1% (n = 14) of patients in the 2 cm, 3 cm and 4 cm groups, respectively. The tumour-specific survival was 100%, 96.9% and 94.6% at 1 year, 97.5%, 90.3% and 87.5% at 5 years and 97.5%, 87.3% and 84.1% at 10 years for the 2 cm, 3 cm and 4 cm groups, respectively (p < 0.05). - CONCLUSIONS: Negative prognostic features as well as worse oncological outcome increase with tumour diameter above 2 cm. These data have important implications when considering active surveillance of small renal tumours.